PENGARUH KOMUNIKASI ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN TETAP PADA PT. MAH SING INDONESIA - Shinta Vesmagita (Universitas Mercu Buana, 2015)
In achieving its objectives, PT. Mah Sing Indonesia should consider factors that can affect the performance of the employee. Among them are communication and work environment. Conditions of work environment and communication greatly affect the performance of an employee. The research is aimed to know: 1) the effect of organization communication influences on permanent employee's performance, 2) the effect of working environment influences on permanent employee's performance, and 3) together with organization communication and work environment influence on permanent employee's performance. The population in this study was the total number of permanent employee of PT. Mah Sing Indonesia. Of this population will be drawn sample used in this study as respondents. Sampling technique in this study using convenience purposive sampling. By using Slovin formula it can be seen the number of sample. The method of analysis used by the authors is the Multiple Linear Regression Analysis, the t-test, and F-test.Keywords: Communication, Work Environment and Employee Performance